FISCAL DECENTRALIZATION POLICY IN IMPROVING THE REGIONAL ECONOMY: A SPATIAL ECONOMETRIC APPROACH - Yusuf, Nurjannah - (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2020)
Indonesia faced the problem of economic inequality and a low level of per capita income, especially in areas producing mining goods and quarries, which are a source of national income. Exports for these commodities do not affect increasing regional income per capita. This problem became a reason; decentralization is a political policy choice after the fall of the New Order in 1998, as a reform resulting in each region would have space to actualize its regional potential, both economically and politically. Nevertheless, after 20 years of implementation, decentralization, inequality, and poverty in the eastern region have not experienced much change. Also, the decentralized system, especially fiscal decentralization, actually burden of the central government financial, because the provinces are most dependent on central government funds. This study investigates why decentralization does not affect reducing poverty and how it should work. It was using a spatial approach to assess the regional economy for the period 2004-2015 with applied the spatial Durbin model (SDM) panel of data from 33 provinces in Indonesia. The results found that the level of provincial per capita income did not determine by initial income or the amount of transfer fund, but it is by imports and exports. While local revenue government is a source of transfer grant does not impact except much less for growth economic of regional.